FACTORS AFFECTING ADVERTISING AVOIDANCE ON FACEBOOK OF TEENAGERS IN HOCHIMINH CITY - Hồ Trúc Vi; Phan Trọng Nhân (Tạp chí Khoa học Đại học Đà Lạt)
This research aims to discover and confirm the factors that influence the youths’ avoidance of advertising on Facebook. The data were analyzed from 335 young clients in Hochiminh City. The research model and scales were constructed from the theoretical basis of the advertising avoidance by Cho and Cheon (2004); Kelly, Kerr, and Drennan (2010). In this study, the author developed the scales of avoidance behavior from the dimension based on the privacy and the relationship between privacy concern and the avoidance of social networking site by Grubbs and Milne (2010). Quantitative research methods using SPSS were used for analysis in addition to qualitative research at the preliminary stage. The test results show that privacy concerns, impediments to awareness, information overload, and negative experiences are factors that strongly impact advertising avoidance. This is one of the first studies for the avoidance of advertising in Vietnam. Although it has only been empirically tested on Facebook, it has opened new doors for authors who want to learn about this aspect from various views.